Sulfite Oxidase Deficiency – An Unusual Late and Mild Presentation - Rocha, S (2013)
Introduction: Sulfite oxidase deficiency (SOD) is an autosomal recessive inherited disease usually presenting in the neonatal period with severe neurological symptoms including seizures, often refractory to anticonvulsant therapy, and a rapidly progressive encephalopathy resembling neonatal hypoxic ischemia, with premature death. Most patients develop dislocated ocular lenses. Later or milder presentations of SOD are being reported with increasing frequency. These presentations include neurological regression with loss of previously acquired milestones or movement disorders. Case report: We report a four years old girl presenting with intermittent ataxia and uncoordinated limb movements. A similar episode of ataxia had occurred previously, one year before, with complete neurologic recovery and normal developmental milestones. Bilateral lens dislocation had been recently diagnosed. Cranial MRI demonstrated bilateral globus pallidus enhancement. Low homocysteine was found in plasma and SulfitestR was positive. Further investigations led to confirmation of isolated sulfite oxidase deficiency with no enzyme activity detected on skin fibroblasts culture. Discussion: This case illustrates the clinical variability of SOD and it is not only atypical but also seems to be the mildest form described so far. The association of ectopia lentis with a movement disorder, even without psychomotor regression, should prompt us to look for this diagnosis.